Japanese Reflections on World War II and the American Occupation - Porter, Ran Ying; Porter, Edgar A. (Amsterdam University Press, 2017)
This book presents an unforgettable up-close account of the effects of World War II and the subsequent American occupation on Oita prefecture, through firsthand accounts from more than forty Japanese men and women who lived there. The interviewees include students, housewives, nurses, midwives, teachers, journalists, soldiers, sailors, Kamikaze pilots, and munitions factory workers. Their stories range from early, spirited support for the war through the devastating losses of friends and family members to air raids and into periods of hunger and fear of the American occupiers. The personal accounts are buttressed by archival materials; the result is an unprecedented picture of the war as experienced in a single region of Japan.
Description based on print version record.
KU Select 2018: HSS Backlist Books
Keywords: History / Asia / Japan; History; Electronic books